EP-EMA Regimen (Etoposide and Cisplatin With Etoposide, Methotrexate, and Dactinomycin) in a Series of 18 Women With Gestational Trophoblastic Neoplasia. Issue 5 (1st June 2012) - Han, Sileny N.; Amant, Frédéric; Leunen, Karin; Devi, Uma K.; Neven, Patrick; Vergote, Ignace
Abstract : Objective: Evaluation of toxicity and outcome of high-risk gestational trophoblastic neoplasia when treated with EP-EMA (etoposide, 150 mg/m 2 ; cisplatin, 75 mg/m 2, intravenous, day 1; etoposide, 100 mg/m 2 ; methotrexate, 300 mg/m 2 ; dactinomycin, 0.5 mg, intravenous, day 8, every two weeks). Materials and Methods: We conducted a retrospective chart review of the period 2004–2010. The first-line chemotherapy regimen for high-risk gestational tropholdastic neoplasia was EP-EMA. Results: Eighteen patients were treated with EP-EMA, either as first-line chemotherapy for high-risk gestational trophoblastic neoplasia (n = 6), placental site trophoblastic tumor (n = 1), or as salvage chemotherapy for gestational trophoblastic neoplasia after single-agent methotrexate (methotrexate, 1 mg/kg, on days 1, 3, 5, and 7 every two weeks) (n = 10) or high-dose methotrexate-etoposide: methotrexate, 1000 mg/m 2, on day 1; etoposide, 100 mg/m 2, on days 1 to 2, every week) (n = 1). Median number of cycles of EP-EMA was 8 (range, 3–11). Median follow-up was 19 months (range, 7–77 months). Concerning response rate, 16 patients (89%) achieved complete remission without disease recurrence. Two patients (11%) died: One patient with placental site trophoblastic tumor died of progressive disease; the second patient presented with choriocarcinoma, primarily metastasized to liver, lung, skin, kidney, and brain. She died of sepsis and endocarditis after adding intrathecal methotrexate and switching cisplatin to carboplatin in the EP-EMA regimen. Toxicity was significant. Eight treatment changes were made owing to grade 2 to grade 3 ototoxicity: 7 to high-dose methotrexate-etoposide, 1 change of cisplatin to carboplatin. Fifteen patients (83%) experienced grade 3/4 neutropenia.